Early-Life Nutrition Interventions Improved Growth Performance and Intestinal Health via the Gut Microbiota in Piglets - Luo, Chengzeng; Xia, Bing; Zhong, Ruqing; Shen, Dan; Li, Jiaheng; Chen, Liang; Zhang, Hongfu (Frontiers in Nutrition, 2022)
The intestinal problem of piglets is the main cause of morbidity before and after weaning. However, the references regarding how pre-weaning and post-weaning nutritional strategies can be combined with sustain optimal gut health are inadequate. To fulfill this gap, we studied the effects of early-life nutrition interventions through synthetic milk on the growth performance and gut health in piglets from 3 to 30 days of age. Twelve sows were randomly allocated into control group (CON) and early-life nutrition interventions group (ENI). All the piglets were fed with the same kind of creep diets ad libitum from 7 days of age and the piglets of ENI group were supplied extra synthetic milk from 3 to 30 days of age. The results showed that early-life nutrition interventions improved (P < 0.05) the growth performance, liver weight, spleen weight, and reduced diarrhea rate of piglets after weaning. The early-life nutrition interventions significantly up-regulated (P < 0.05) the relative mRNA expression levels of ZO-1, Occludin, Claudin4, GALNT1, B3GNT6, and MUC2 in colonic mucosa and reduced (P < 0.05) the activity of alkline phosphatase (AKP) in serum and the content of lipopolysaccharides (LPS) in plasma. The number of goblet cells and crypt depth of colon were significantly higher (P < 0.05) for piglets in ENI group. In addition, the relative mRNA expression levels of MCP-1, TNF-α, IL-1β, and IL-8 and the protein expression levels of TNF-α, IL-6, and IL-8 of colonic mucosa in ENI group were decreased (P < 0.05). The relative abundance of Lactobacillus in colonic chyme and mucosa for piglets in ENI group were all geater than those in CON group (P < 0.05). The correlation analysis demonstrated that Lactobacillus was positively correlated with the relative mRNA expression levels of ZO-1, Claudin4, and GALNT1 and negatively correlated with the level of MCP-1 in colonic chyme and mucosa. In summary, this study showed that early-life nutrition interventions improved growth performance, colonic barrier, and reduced the inflammation in colon via the gut microbiota in piglets. Early-life nutrition intervention through supplemental synthetic milk is a feasible measure to improve health and reduce deaths of piglets.